A Review and Clinical Practice Guideline for Health Professionals Working With Indigenous and Culturally and Linguistically Diverse (CALD) Populations During COVID-19 - Kayrouz, Rony; Schofield, Carlie; Nielssen, Olav; Karin, Eyal; Staples, Lauren; Titov, Nickolai (Frontiers in Public Health, 2021)
Background: As the rates of infection and mortality from COVID-19 have been higher in minority groups, the communication of health information in a way that is understood and accepted is of particular importance. Aims: To provide health professionals with a clinical practice guideline for clear and culturally sensitive communication of health information about COVID-19 to people of Indigenous and culturally and linguistically diverse (CALD) backgrounds. Assessment of Guideline Options: A review of the literature on health communication was conducted, and the guidelines were developed with particular reference to the SPIKES protocol of ‘breaking bad news’ in oncology and the use of the DSM-5 Cultural Formulation Interview (CFI). Actionable Recommendations: The guideline combines two approaches, the Cultural Formulation Interview, developed for DSM-5, and the SPIKES protocol used for delivering “bad news” in oncology. The combined CFI-SPIKES protocol is a six step clinical practice guideline includes the following: (1) Set up (S) the interview ; (2) Determine how the patient perceives the problem (P) using the Cultural Formulation Interview (CFI) to elicit the patient’s cultural perception of the problem; (3) Obtain an invitation (I) from the patient to receive a diagnosis; (4) Provide the patient knowledge (K) of diagnosis in a non-technical way; (5) Address the patient’s emotional reaction (E) to diagnosis ; and (6) Provide the patient a summary (S) of healthcare and treatment. Conclusions and Relevance: This article presents guidelines for assessing the cultural dimensions of patients understanding of COVID-19 and delivering diagnostic and treatment recommendations in ways that are culturally safe and responsive, such as.: (a) suspending the clinician’s own cultural biases in order to understand the explanatory models and cultural values of their CALD or Indigenous patients; (b) encouraging the use interpreters or cultural brokers to ensure that that the message is delivered in a way that the patient can understand.; and (c) encouraging CALD or Indigenous patient to take an active part in the solution and treatment adherence, with the goal of minimising transmission of COVID-19 in CALD and Indigenous communities.